Cell Fixation by Light‐Triggered Release of Glutaraldehyde. (22nd March 2017) - Schelkle, Korwin M.; Schmid, Christopher; Yserentant, Klaus; Bender, Markus; Wacker, Irene; Petzoldt, Martin; Hamburger, Manuel; Herten, Dirk‐Peter; Wombacher, Richard; Schröder, Rasmus R.; Bunz, Uwe H. F.
Abstract: Chemical fixation of living cells for microscopy is commonly achieved by crosslinking of intracellular proteins with dialdehydes prior to examination. We herein report a photocleavable protecting group for glutaraldehyde that results in a light‐triggered and membrane‐permeable fixative, which is nontoxic prior to photocleavage. Lipophilic ester groups allow for diffusion across the cell membrane and intracellular accumulation after enzymatic hydrolysis. Irradiation with UV light releases glutaraldehyde. The in situ generated fixative crosslinks intracellular proteins and preserves and stabilizes the cell so that it is ready for microscopy. In contrast to conventional glutaraldehyde fixation, tissue autofluorescence does not increase after fixation. Caged glutaraldehyde may in future enable functional experiments on living cells under a light microscope in which events of interest can be stopped in spatially confined volumes at defined time points. Samples with individually stopped events could then later be analyzed in ultrastructural studies.